Prevalence of text neck posture, smartphone addiction, and its association with neck disorders among university students in the Kingdom of Saudi Arabia during the COVID-19 pandemic - Mohamed Sherif Sirajudeen; Msaad Alzhrani; Ahmad Alanazi; Mazen Alqahtani; Mohamed Waly; Radhakrishnan Unnikrishnan; Hariraja Muthusamy; Wafa Alrubaia; Nidaa Alanazi; Mohamed K. Seyam; Faizan Kashoo; Mohammad Miraj; et al. (PeerJ, 2022)
The smartphone emerges as an inevitable gadget in modern society and its increased usage results in neck disorders among its users. However, the factors associated with neck disorders among smartphone users are ambiguous and less explored in the literature. The purpose of this research was to determine the prevalence of text neck posture, smartphone addiction/overuse, and its association with neck disorders among university students in the Kingdom of Saudi Arabia during the COVID-19 pandemic. A total of 313 university students who were aged 18 years and older, owned a smartphone, and used it during the preceding 12 months participated in this cross-sectional study. A self-administered questionnaire was used to collect data regarding the prevalence of text neck posture, smartphone addiction/overuse, neck disorders, and the level of physical activity. Binary logistic regression was used to determine the association between the prevalence of neck disorders and text neck posture, smartphone addiction/overuse, and level of physical activity. The 12 months prevalence of neck disorders due to smartphone use among the participants was found to be 46%. The neck disorders were more prevalent among participants who reported text neck posture (P < 0.001) and categorized as smartphone-addicted/overuse (P < 0.001). Measures to promote the awareness of healthy use of smartphones including postural education and to decrease its screen time are warranted to reduce neck disorders.